THE PERFORMANCE OF CHITOSAN-FERRIHIDRYTE MEMBRANE FOR PHOSPHATE UPTAKE - Barlah Rumhayati; Chasan Bisri; Wahyu O. Fajarina (Universitas Gadjah Mada, 2009)
The uptake of orthophosphate onto the chitosan-ferrihydrite membrane has been studied. The membrane was proposed as a new binding layer of DGT technique. Membrane was prepared from a mixture of chitosan solution with ferrihydrite (FeOOH) paste and was crosslinked with glutaraldehyde. As a result, the uptake of orthophosphate was slow. The maximum adsorption capacity was reached at pH 5.0 and 8.0. It was mainly due to electrostatic attraction of phosphate ions to the protonated free amino groups of chitosan and to active sites of ferrihydrite. Desorption could be occurred optimally using 0.3 M of sulphuric acid. The absorption of SO42- ion to the protonated amino groups and the formation of ionic crosslinking could exchange and desorb phosphate ions. Ferrihydrite was eluted also by the acid. However, the eluted ferrihydrite readsorbed phosphate ions, resulted in minimizing the analysed free phosphate.